Information theoretic analysis of Landau levels in monolayer phosphorene under magnetic and electric fields. (11th September 2019) - Castaños, Octavio; Romera, Elvira; Calixto, Manuel
Abstract: We analyze the structure of phosphorene Landau energy levels under electric and magnetic fields perpendicular to the material sheet. The electric field Δ provides a tunable band gap, and a topological phase transition occurs at a critical value Δ c . Low energy Landau levels and edge states are analyzed with different information theoretic measures (like participation ratio, fidelity and entropy) and some order parameters, which turn out to be good markers of the topological phase transition.